The Different Faces of Religion in Therapy: An Exploratory Qualitative Study of a Religion-Based Therapeutic Community for Addiction Recovery in Israel - Pagis, Michal (Journal of religion and health, 2025)
This article examines the impact of the integration of religion and psychological treatment in a religion-based therapeutic community for persons in recovery from addiction in Israel. Based on an exploratory qualitative study that includes participant observation in a Jewish forgiveness therapy training course and in-depth interviews with counselors working in the community, we identify three themes that characterize the therapeutic process. First, religion emerges as a challenge in therapy, one that should be addressed with sensitivity. Second, religion can be turned into a spiritual and cultural resource in the recovery process, with a cautious and sensitive approach. Third, religion can offer a remedial experience, without necessarily involving an intensification of faith. We offer principles that can help guide decisions regarding the integration of religion into therapy, with a focus on addiction treatment oriented to clients with a religious background.